Penerapan Kontroler ANFIS untuk Load Frequency Control - Dewanto, Agustinus Bayu; Bachtiar, Rochmad Yunus; Setiawan, Fandi; Saraswati, Ni Made Omiku Radha; Hermawan, Andhika; Ardiansyah, Afrizal; Hutama, Ilham Riza; Pambudi, Wahyu Setyo; Muni, Misbahul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Load Frequency Control (LFC) is a system that works as a unit with the boiler-turbine-generator system which functions to maintain a frequency of 50 HZ by giving control to the governor system at the power plant when the peak load position results in a decrease in frequency, later LFC instructs the turbine governor to open a valve to drain the steam generated from the boiler system. In this study, we compared the performance of two controllers on LFC, namely PID and ANFIS through Matlab simulations. The simulation results show that the Setlling Time of the ANFIS Mamounia control is 76% faster than the PID control. ANFIS control can respond to changes in load to steady state frequency conditions with an error of 0.6% which is more effective than the PID control.